Enzymatic synthesis of N-succinyl chitosan-collagen peptide copolymer and its characterization. (15th June 2017) - Xiao, Yao; Ge, Hongyu; Zou, Shengqiong; Wen, Huigao; Li, Ya; Fan, Lihong; Xiao, Lingling
Highlights: Collagen peptide grafted N -succinyl chitosan contributed to improving the antioxidant activity. NSC-COP was prepared by using MTGase as biocatalyst. MTT assay exhibited that at a suitable concentration NSC-COP could promote L929 mouse fibroblasts effectively. Abstract: Collagen peptide (COP) grafted N -succinyl chitosan (NSC) was prepared by using microbial transglutaminase (MTGase) as biocatalyst. The catalyzed reaction displayed high efficiency, high selectivity, mild reaction condition and environmental friendliness. The degree of substitution (DS) of N -succinyl chitosan-collagen peptide (NSC-COP)depended on the reaction time, the reaction temperature, the mass ratio of COP to NSC and the mass ratio of MTGase to NSC. NSC-COP showed excellent moisture absorption and retention properties. Antioxidant activities of varying DS and concentration of NSC-COP were evaluated using 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and hydroxyl. Methylthiazol tetrazolium (MTT) assay exhibited that at a suitable concentration NSC-COP with different DS value could promote L929 mouse fibroblasts effectively. The animal experiment indicated that the wound covered with NSC-COP were completely filled with new epithelium within 2 weeks without any significant adverse side reactions. Therefore, the results may contribute to finding the application of NSC-COP in pharmaceutical and biomedical fields.